Patient Satisfaction and Visual Performance in Patients with Ocular Pathology after Bilateral Implantation of a New Extended Depth of Focus Intraocular Lens - Laureano A. Rementería-Capelo; Pilar Lorente; Virginia Carrillo; José M. Sánchez-Pina; Javier Ruiz-Alcocer; Inés Contreras (Journal of Ophthalmology)
Aim. To evaluate visual results and patient-perceived outcomes in patients with ocular pathologies implanted with a new extended depth-of-focus intraocular lens (IOL). Methods. Patients with ocular pathology undergoing cataract surgery and bilaterally implanted with Vivity® IOLs were evaluated three months after surgery. The control group included patients with no ocular pathologies. Binocular defocus curves, corrected and uncorrected mono- and binocular distance visual acuity (DVA), and binocular contrast sensitivity were measured. Patients completed the Catquest-9SF questionnaire and reported on dysphotopsia and their need for spectacle-correction. Results. Twenty-five patients were included in each group. Monocular uncorrected DVA was better in the control group (−0.01 ± 0.07) compared with the study group (0.03 ± 0.08), p=0.027. There were no other statistically significant differences in DVA, with an uncorrected binocular acuity of −0.06 ± 0.06 for the control group and −0.05 ± 0.06 for the study group. Binocular defocus curves were similar for both groups and there were no differences in contrast sensitivity values. Pooling the refractive results, 96% of eyes were within ±0.50 D of target refraction. Seventy percent of patients in the control group reported no halos, compared with 40% in the study group, p=0.047. In both groups, 40% of patients reported being completely spectacle-independent, with the other 60% requiring glasses for near vision always or often. All patients reported being fairly or very satisfied with their vision. Conclusion. Initial results of visual function after Vivity implantation in patients with ocular pathologies are encouraging, with high patient satisfaction and few difficulties for daily activities.